A contribution to the study of the history and architecture of the 'Rosija' Insurance Company building in Belgrade (1904-1908) - Andrić Dunja; Kiproski Sanja (Nasleđe)
At the beginning of the 20th century, an ambitious project for the construction of the palace of the 'Rosija' ('Russia') Insurance Company was realized along Terazije, one of the most important transects within Belgrade's urban fabric. Built in the spirit of the Vienna Secession movement, with its height and volumetric characteristics, the edifice embodied the urban development of Terazije and became a recognizable visual topos of the capital of the Kingdom of Serbia. Created through the utilization of modern materials, and as a result of fruitful cooperation between Russian architects and renowned Serbian architect Jovan Ilkić (1857-1917), the palace of the 'Rosija' Insurance Company came to symbolize the modern identity of Belgrade. Despite the great architectural-urbanistic and socio-cultural significance of this major structure, certain elements related to its construction have not yet been fully explored. In particular, the competition for the architectural solution remained insufficiently studied. Therefore, the aim of this paper is to highlight new data related to the history of the construction of the 'Rosija' Insurance Company building and encourage new interpretations and further valorization of its architectural solution.